Police pursuing justice: reframing law enforcement for the twenty-first century - Bennett, Samantha L. (Policing perspectives and challenges in the twenty-first century, 2023)
"Using Pennsylvania as a case-study, this book examines how BARJ legislation "trickles down" to the law enforcement level and affects police officer behavior, discretion, and decision-making processes"--